Unraveling the Mesozoic and Cenozoic Tectonothermal Evolution of the Eastern Basque‐Cantabrian Zone–Western Pyrenees by Low‐Temperature Thermochronology. Issue 9 (24th September 2019) - DeFelipe, I.; Pedreira, D.; Pulgar, J. A.; van der Beek, P. A.; Bernet, M.; Pik, R.
Abstract: Low‐temperature thermochronology studies have increased our knowledge of the orogenic processes along the Pyrenean‐Cantabrian mountain belt by placing time constraints on the exhumation history of its rocks. However, a significant gap in the data existed between the western Pyrenees and the central Cantabrian Mountains, hampering a comprehensive view of the tectonothermal evolution along the belt. We present a new apatite fission track and zircon (U‐Th)/He (ZHe) data set for the eastern Basque‐Cantabrian zone–western Pyrenees. Apatite fission track central ages cluster in the Eocene‐Oligocene. ZHe samples can be separated into two groups: Group 1 depicts clustered ZHe ages‐eU concentration (Cinco Villas massif) and Group 2 depicts dispersed ZHe ages‐eU concentration (Alduides massif and a Paleozoic rock pinned along the Leiza thrust). A sample from the Oroz‐Betelu massif shows intermediate behavior. Inverse modeling suggests that samples from Group 1 reached 240–280 °C in the Late Cretaceous, implying deep sedimentary burial of the Cinco Villas massif before its major exhumation phase, most probably in the early to middle Eocene, postdating the phase of rapid exhumation of the western part of the Leiza thrust. The sample from the Oroz‐Betelu massif, far from the Mesozoic exhumed mantle domain, experienced maximum temperatures close to 200 °C by burial beneath the Jaca‐Pamplona basin. It was later exhumed in the hanging wall of the Gavarnie thrust in the Bartonian‐Priabonian. This work provides new insights into the tectonothermal evolution of the Basque massifs and the inversion of a hyperextended margin. Key Points: The Cinco Villas massif was buried beneath several kilometers of Mesozoic sediments and was exhumed in the early‐middle Eocene by a S vergent fault The Oroz‐Betelu massif was buried below the Pamplona basin before experiencing a rapid exhumation in the Bartonian‐Priabonian The Leiza extensional detachment (eastern Basque‐Cantabrian basin) was reactivated as a thrust system in the early Eocene